Comprehensive evaluation of pelvic floor disorders - Md Nor, Azmi (2011)
Pelvic floor disorders are an underdiagnosed source of morbidity and decreased quality of life for women while it is a much less common disorder in men. Almost 24% of women in the United States report at least one pelvic floor disorder, which, unfortunately, increases with age, parity and obesity. The demand or pelvic floor services is expected to grow as the relative proportion of the elderly increases and physicians become more aware of these disorders. Pelvic Floor Disorders incorporate a spectrum of symptoms which include constipation, fecal incontinence, pelvic organ prolapse and urinary incontinence which involve the central and posterior compartments of the pelvic floor. There are various etiologies involved varying from systemic illnesses to neuromuscular disturbances of the gastrointestinal tract. A careful history and physical examination is key to establishing a provisional diagnosis and directing diagnostic testing. Often, patients present with vague complaints and it is vital that a careful description of the patient’s symptoms in their own words be obtained to better define the clinical scenario. It is increasingly recognized that patients with pelvic floor complaints benefit from a multidisciplinary evaluation focusing on colorectal, gynaecological and urological surgical care. Each pelvic floor complaint has a high propensity to coexist with others, making multispecialty evaluation and care essential. Even for those patients without defined anatomical defects, functional disorders of the gastrointestinal tract or pelvic floor unrelated to prior obstetric experience are also common. Numerous advances in radiological and physiological investigatory techniques have become available to clinicians. Comprehensive pelvic floor testing in a stand-alone laboratory facilitates this evaluation, and is very efficient and convenient process for patients. This can enable the underlying pathogenesis of the condition can be determined, which in turn aid diagnosis and guide medical, behavioral and surgical treatment. Tests germane to the posterior pelvis and frequently used by the colorectal surgeons will be the emphasis of this presentation.